Analisis Pemanfaatan Teknologi dalam Pembelajaran Bahasa Inggris di Kelas XI E SMA N 2 Bangli - Ni Wayan Artiniasih; Luh Made Dwi Wedayanthi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to analyze the use of technology in English language learning in Class XI E at SMA N 2 Bangli. The technologies used include laptops, LCD projectors, and applications such as Kahoot, Quizizz, and PowerPoint. The research employs a descriptive qualitative approach, with data collection techniques consisting of observation, checklists, and field notes. The results show that the use of technology helps to enhance students' motivation and engagement in learning. Students become more active, and the learning process becomes more interesting due to the use of visual and digital media. However, some challenges include limited access to technology for some students and technical issues such as unstable internet connections. This study suggests improving the school's technological infrastructure and providing training for teachers to effectively integrate technology into the classroom. With adequate support, the use of technology can significantly improve the quality of English language learning.